2015
DOI: 10.1161/circimaging.114.002666
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Stress Myocardial Perfusion Imaging Compared to Invasive Coronary Angiography With Fractional Flow Reserve Meta-Analysis

Abstract: Background— Hemodynamically significant coronary artery disease is an important indication for revascularization. Stress myocardial perfusion imaging is a noninvasive alternative to invasive fractional flow reserve for evaluating hemodynamically significant coronary artery disease. The aim was to determine the diagnostic accuracy of myocardial perfusion imaging by single-photon emission computed tomography, echocardiography, MRI, positron emission tomography, and computed tomography compared with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(204 citation statements)
references
References 45 publications
(20 reference statements)
6
170
1
10
Order By: Relevance
“…Previous multicenter, multivendor head-to-head comparison trials have suggested that perfusion MRI is a valuable alternative to SPECT for the detection of significant anatomic CAD, with superior diagnostic performance, especially in multivessel disease (17)(18)(19). In a recent metaanalysis, myocardial perfusion MRI demonstrated a sensitivity of 89% and specificity of 87% for the diagnosis of hemodynamically significant CAD using a X-ray coronary angiography with fractional flow reserve as a reference standard on a per-patient level, which are similar to those of PET (84% and 87%, respectively) and superior to those of SPECT (74% and 79%, respectively) (20). In addition, vasodilator stress myocardial perfusion MRI provides prognostic value in patients with biomarker negative angina and reclassifies risk in patients with prior CAD (21,22).…”
Section: Assessment Of Myocardial Perfusionmentioning
confidence: 96%
“…Previous multicenter, multivendor head-to-head comparison trials have suggested that perfusion MRI is a valuable alternative to SPECT for the detection of significant anatomic CAD, with superior diagnostic performance, especially in multivessel disease (17)(18)(19). In a recent metaanalysis, myocardial perfusion MRI demonstrated a sensitivity of 89% and specificity of 87% for the diagnosis of hemodynamically significant CAD using a X-ray coronary angiography with fractional flow reserve as a reference standard on a per-patient level, which are similar to those of PET (84% and 87%, respectively) and superior to those of SPECT (74% and 79%, respectively) (20). In addition, vasodilator stress myocardial perfusion MRI provides prognostic value in patients with biomarker negative angina and reclassifies risk in patients with prior CAD (21,22).…”
Section: Assessment Of Myocardial Perfusionmentioning
confidence: 96%
“…A recent meta-analysis (Table 1) highlighted the inferior accuracy of MPI and stress echocardiography to CTA alone for identifying invasive FFR of ≤0.80 and may explain the better outcomes discussed above for CTA-guided treatment. 28 In addition, in a study of 67 patients with multivessel disease, MPI was particularly suboptimal, with 61% sensitivity, 69% specificity, 47% positive predictive value (PPV), and 80% negative predictive value (NPV). 29 Interestingly, stress MRI and positron emission tomography (PET) performed at least as well as CTA alone, but these technologies are expensive and are not widely used.…”
Section: Why We Need Ct-ffrmentioning
confidence: 99%
“…When compared with invasive coronary angiography with fractional flow reserve, sensitivity is maintained but specificity is lower (61%). 5 Regardless, the prognostic value of normal MPS is well recognized, with an annual coronary event rate\1%. 6 Although such patients may be further stratified by anatomical tests such as invasive or CT coronary angiography, patients with a normal study can usually be reassured without the need for further testing.…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages may explain in part the performance of SPECT MPS in modern comparisons with other techniques such as CMR 12 and fractional flow reserve. 5 Positron emission tomography (PET) MPS has many of the virtues of SPECT and it is often considered to be superior because of its spatial resolution and the ability to quantify perfusion in absolute terms. However, proposing PET as a routine replacement for SPECT requires several questions to be answered: …”
Section: Introductionmentioning
confidence: 99%